1986
DOI: 10.3347/kjp.1986.24.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of natural human infection by Echinostoma hortense

Abstract: Two cases of human Echinostoma hortense infection were found in Seoul Paik Hospital. Their stools revealed echinostomatid eggs. After treatment with praziquantel (single does of 10-12 mg/kg) and purgation with magnesium salt, total 21 flukes were collected in one case. The flukes were 5.9-7.5 mm long, had 27-28 collar spines around their head, laterally deviated ovary and two tandem testes. They were identified as E. hortense Asada, 1926. The cases are 38-year and 20-year old men residing in Seoul, whose homet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In consideration of the pathologic findings, the symptoms experienced by the present patient, i.e., epigastric pain and abdominal discomfort, might be provoked by the abrasive action of E. hortense. The frequent symptoms reported by infected individuals, though not pathogen-specific, are abdominal pain, cramps, anorexia, postprandial burning, flatulence, and diarrhea (Lee et al, 1986a;Chai et al, 1994;Lee and Hong, 2002). It has also been suggested that chronic and severe infection may cause intestinal villous atrophy and lead to manifestations of malabsorption.…”
Section: Discussionmentioning
confidence: 99%
“…In consideration of the pathologic findings, the symptoms experienced by the present patient, i.e., epigastric pain and abdominal discomfort, might be provoked by the abrasive action of E. hortense. The frequent symptoms reported by infected individuals, though not pathogen-specific, are abdominal pain, cramps, anorexia, postprandial burning, flatulence, and diarrhea (Lee et al, 1986a;Chai et al, 1994;Lee and Hong, 2002). It has also been suggested that chronic and severe infection may cause intestinal villous atrophy and lead to manifestations of malabsorption.…”
Section: Discussionmentioning
confidence: 99%
“…Patients infected with echinostome species suffer from abdominal pain, diarrhea, tenesmus, easy fatiguability, loss of body weight, and urinary incontinence [1,2,73,380]. The severity of symptoms is generally stronger than those seen in other intestinal fluke infections, such as heterophyids [5].…”
Section: Echinostomesmentioning
confidence: 99%
“…Among these genera, Echinostoma is the largest one, which constitutes 7 species, including E. hortense , E. angustitestis , E. cinetorchis , E. echinatum , E. ilocanum , E. macrorchis , and E. revolutum [ 2 ]. Although the majority of people infected by echinostomes have no obvious symptoms, severe infections may cause anorexia, lower extremity edema, anemia, weight loss, and dysplasia [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The adult worms of E. hortense often inhabit the small intestine of humans and many animals [ 3 ]. The parasitic fluke E. hortense was originally described from rats in Japan [ 4 ], and since then, it has been reported in South Korea and China [ 2 , 3 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation